中国成年人BMI与血浆氨基酸和酰基肉碱水平关联的观察性和孟德尔随机化研究 - Cheng, S; Wu, T; Yu, C; Sun, D; Pei, P; Du, H; Chen, J; Chen, Z; Pang, Y; Lyu, J; Li, L (Zhonghua Yixuehui, Chinese Medical Association, 2024)
Objective To explore the relationship between BMI and levels of plasma amino acids and acylcarnitines in Chinese adults.